INTEGRATED TACTICALS TIMETABLES – PART I (Perner's Contacts, 2021)
This technical article will acquaint readers with the beginning of the aplicated integrated tacticals timetables and with the basic concepts that are used in the integrated tacticals timetables. The article will also mention Mathematical calculations for the introduction of stop trains with full reach of stopping places.
Keywords: traffic; interval; integrated tacticals timetables